The Influence of The Congress Party on The Muslim League in India 1906 – 1947 - Saputra, Permadi; Setiawati, Elis; Hartati, Umi; Akmal, Atqo (Swarnadwipa, 2025)
This study aims to: (1) Analyze the history of the founding of the Congress Party and the Muslim League (2) Analyze the development of the Congress Party and the Muslim League (3) Analyze the struggle of the Congress Party and the Muslim League to achieve independence in India (4) Analyze the influence of the Congress Party and the League Muslim Muslims to achieve Independence in India in 1906-1947. This research uses historical methods. Data collection techniques were carried out using heuristic methods and literature studies. The findings of this research regarding the Influence of the Congress Party on the Muslim League in India in 1906-1947 show that the beginning of the founding of the Congress Party and the Muslim League was the result of their efforts in approaching British colonialism. However, in the process of development, the Congress Party and the Muslim League have encountered their own problems. In the end, the Congress Party and the Muslim League worked together to fight for independence in India from British rule and gave them the right to form their respective countries, namely India and Pakistan.